Analisis Multi-Attribute Decision Making Sebagai Perankingan Wilayah Produktif Penghasil Kelapa Sawit di Provinsi Riau - Yendra Afriza; Mustakim Mustakim (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Riau Province has the potential to utilize oil palm cesspit as a renewable energy source. Therefore, there should be a ranking for the region of palm oil producer in Riau Province in order to provide information and recommendations to the government on policy in determining the center development of renewable energy in Riau Province, give the investment opportunities in agriculture, develop the production of palm oil in the region that has a fewer palm tree and provide solutions to overcome the problems of selection and ranking manually. Simple Aditive Weighting (SAW) algorythm, weighting Product (WP) and Technique for Order Preference by Similarity to Ideal solution (TOPSIS) are used to perform the rankings districts with using a weighting in the form of direct weights, fuzzy and percentage (%). For maximum results which is accurate and fit the expected results, applied three methods that have a role to determine the best method in making decisions. The results of the third calculation method of the third weighting generate is discovered that SAW method have a better weight percentage than WP and TOPSIS methods. Based on the calculation of weight percentage using SAW method, Tapung region, Pangkalan Kuras, Mandau, Tapung Hilir and North Tambusai occupy the top 5 rank as the potential area of renewable energy sources.